Preparation method and application of non-stoichiometric nano copper sulfide

The preparation of non-stoichiometric nano copper sulfide by the liquid phase method of room temperature and pressure was solved, and the catalytic activity of polysulfide redox reaction was achieved, and the performance of efficient polysulfide-based liquid flow batteries was improved, with good commercial prospects.

CN120364741APending Publication Date: 2025-07-25深圳市中和储能科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510295066.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

In the prior art, the electrode catalytic activity of polysulfide redox reaction is limited, and the precious metal catalyst is costly and easy to fall off, and the carbon electrode modification fails quickly, resulting in limited energy efficiency and power density of sulfur-based liquid flow batteries.

Method used

Non-stoichiometric copper sulfide was prepared by the normal temperature and pressure liquid phase method. Through precise control of copper salt and doped element solution, uniform nanoparticles were generated as the negative electrode catalyst of polysulfide-based liquid flow battery.

Benefits of technology

The preparation of high-performance non-stoichiometric nano copper sulfide catalyst is realized, the specific capacity and energy density of polysulfide-based flow batteries are improved, and the circulation performance is excellent, the production cost is reduced and batch production is easy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364741A_ABST
    Figure CN120364741A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polysulfide-based flow battery materials, and discloses a preparation method of non-stoichiometric nano copper sulfide, which comprises the following steps: preparing a sulfur ion-containing compound into a solution to obtain a first precursor solution; copper salt and salt containing doping elements are prepared into a solution, and a second precursor solution is obtained; dropwise adding the second precursor solution into the first precursor solution, continuously stirring the first precursor solution at the same time, and performing suction filtration on an obtained reactant to obtain the non-stoichiometric nano copper sulfide. The invention also discloses an application of the non-stoichiometric nano copper sulfide. According to the invention, the preparation of the high-performance non-stoichiometric nano copper sulfide catalyst is realized through a multi-parameter coordinated regulation and control technology, and it is ensured that when the prepared non-stoichiometric nano copper sulfide catalyst is prepared into a polysulfide-based flow battery negative electrode for a polysulfide-based flow battery; the polysulfide-based flow battery has high specific capacity and energy density, excellent cycle performance and good commercial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polysulfide-based flow battery materials, and particularly relates to a preparation method and application of non-stoichiometric copper sulfide nanoparticles. Background Art

[0002] The excessive consumption of fossil energy has led to a sharp increase in greenhouse gas emissions and deterioration of the ecological environment. Accelerating the large-scale application of renewable energy sources such as wind energy and solar energy has become a global consensus. However, the power generation of renewable energy sources such as wind and light is characterized by significant intermittency and volatility. Direct grid connection will threaten the stable operation of the power system. There is an urgent need to develop efficient and long-life large-scale energy storage technologies to achieve the smooth output of renewable energy and the frequency regulation requirements of the power grid.

[0003] Flow batteries are regarded as one of the most promising large-scale energy storage technologies due to their advantages such as decoupled power and capacity design, long cycle life, and high safety. Among them, all-vanadium flow batteries have been commercially applied, but their development is limited by the scarcity of vanadium resources, high cost of electrolytes, and corrosion of equipment by strong acidic electrolytes. In contrast, sulfur-based flow batteries (such as sulfur / iron, polysulfide / bromine systems) use low-cost polysulfides as negative electrolytes and achieve energy storage through the valence change of polysulfides. Their electrolyte raw materials are rich and the cost is only 10% - 20% of the all-vanadium system, showing significant economic advantages. However, the polysulfide redox reaction involves a multi-electron transfer process, and its inherent reaction kinetic retardation leads to high charge transfer resistance and large polarization loss, seriously restricting the energy efficiency and power density of the battery, and becoming the core bottleneck for the commercial application of sulfur-based flow batteries.

[0004] As the key carrier of the polysulfide redox reaction, the catalytic activity and stability of the electrode directly affect the battery performance. Existing technologies generally use carbon felt, graphite felt and other carbon electrodes, but their original surface has high chemical inertness and limited catalytic activity for polysulfides. Although the electrode activity can be improved by acid treatment, plasma modification or loading with noble metals (such as Pt, Ru), these methods have problems such as complex processes, sharp cost increases, or easy detachment of the catalyst. For example, although noble metal catalysts can reduce the reaction activation energy, their high cost and sulfide poisoning effect lead to a sharp drop in cycle stability; while the modification of oxygen-containing functional groups on the carbon material surface can enhance interfacial adsorption, but the functional groups are prone to decomposition and failure during long-term operation. Therefore, developing non-precious metal electrode materials with high catalytic activity, strong stability and low cost has become the core research direction for breaking through the performance bottleneck of sulfur-based flow batteries. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the above-mentioned deficiencies and defects in the background art, and provide a method for preparing non-stoichiometric copper sulfide nanoparticles by liquid phase at normal temperature and pressure and its application.

[0006] To solve the above technical problems, the technical solution proposed by the present invention is as follows: A method for preparing non-stoichiometric nano copper sulfide, comprising the following steps: (1) Prepare a solution of a sulfur ion-containing compound to obtain a first precursor solution; (2) Prepare a solution of a copper salt and a salt containing a doping element to obtain a second precursor solution; (3) Drop the second precursor solution into the first precursor solution while continuously stirring the first precursor solution; (4) Filter the reactant obtained in step (3) to obtain the non-stoichiometric nano copper sulfide.

[0007] In the above preparation method, preferably, in step (1), the pH value of the first precursor solution is 11 to 13; the pH of the first precursor solution is adjusted using sodium hydroxide or potassium hydroxide solution.

[0008] In the above preparation method, preferably, in step (2), the pH value of the second precursor solution is 1.5 to 2.5; the pH of the second precursor solution is adjusted using dilute nitric acid.

[0009] In the above preparation method, preferably, in steps (1) and (2), the solvent for preparing the solution is deionized water or an organic solvent, and the organic solvent options include methanol, ethanol, or phenol.

[0010] In the above preparation method, preferably, the sulfur ion-containing compound is selected from at least one of sodium sulfide, potassium sulfide, or ammonium sulfide; The copper salt is selected from at least one of copper sulfate, copper nitrate, or copper chloride; The salt containing a doping element is selected from at least one of zinc sulfate, zinc nitrate, zinc chloride, magnesium nitrate, aluminum nitrate, aluminum sulfate, aluminum chloride, iron nitrate, iron sulfate, iron chloride, manganese nitrate, manganese sulfate, or silver nitrate.

[0011] In the above preparation method, preferably, in step (2), the molar ratio of the copper salt to the salt containing a doping element is 1:0.001 to 1:0.8. Further, the molar ratio of the copper salt to the salt containing a doping element is 100:(1 - 9).

[0012] In the above preparation method, preferably, the concentration of the sulfur ion-containing compound in the first precursor solution is 0.1 - 0.2 M; the concentration of the copper salt in the second precursor solution is 0.1 - 0.2 M. This concentration range can ensure the matching of the release rates of sulfur ions (S²⁻) and copper ions (Cu²⁺), avoid the reaction getting out of control due to the excess of a certain ion, achieve the balance of the nucleation and growth processes, and generate nanoparticles with uniform particle size and good dispersibility. Too high a concentration will lead to particle coarsening; too low a concentration is prone to form irregular aggregates.

[0013] In the above preparation method, preferably, in step (3), the volume ratio of the first precursor solution to the second precursor solution is (50 - 60):(40 - 50). The volume of the first precursor solution is slightly higher to ensure that sulfur ions are always in excess when the copper salt solution is dropped, and maintain uniform nucleation at the reaction interface. If the volume ratio is unbalanced, local supersaturation will be triggered, resulting in particle coarsening or the formation of impurity phases; the dropping rate of the second precursor solution is 2 - 3 seconds / drop, and the stirring rate is 450 - 550 r / min; when the second precursor solution is slowly dropped into the first precursor solution, it can ensure a gentle concentration gradient of Cu²⁺ / S²⁻ ions at the reaction interface, avoid explosive nucleation caused by local supersaturation, and rapid dropping or direct mixing will lead to the formation of coarse particles.

[0014] In the above preparation method, preferably, in step (3), the precipitate obtained after suction filtration is dried and ground. Among them, the drying temperature is 50 - 80 °C, the drying time is 22 - 26 h, and the grinding time is 10 - 15 min.

[0015] As a general inventive concept, the present invention also provides a negative electrode of a polysulfide-based flow battery, which is prepared into an electrode using the non-stoichiometric nano copper sulfide prepared by the above preparation method as a catalyst.

[0016] Furthermore, the specific process of preparing an electrode using the non-stoichiometric nano copper sulfide prepared by the above preparation method as a catalyst includes: S1. Disperse the non-stoichiometric nano copper sulfide as a catalyst into a mixed solution of an organic solvent and Nafion and perform ultrasonic oscillation; S2. Uniformly drop the dispersed slurry onto a carbonaceous electrode; S3. Dry the redox electrode after the dropping in S2 is completed to obtain the electrode.

[0017] In the above preparation method, preferably, in S1, the catalyst loading amount is 0.4 - 12 mg / cm 2 .

[0018] In the above preparation method, preferably, in S1, the organic solvent is at least one of methanol, ethanol, ethylene glycol, isopropanol, and butanol.

[0019] In the above preparation method, preferably, in S1, the volume ratio of the mixed solution of the organic solvent to Nafion is 100:0.01 to 1.

[0020] In the above preparation method, preferably, in S2, the mass content of the slurry is 0.5 to 10 mg / mL.

[0021] In the above preparation method, preferably, in S2, the carbonaceous electrode is any one of carbon felt, graphite felt, carbon paper, graphite paper, carbon cloth, and graphite cloth.

[0022] In the above preparation method, preferably, in S3, the drying temperature is 50 to 70 °C and the drying time is 12 to 24 h.

[0023] As a general inventive concept, the present invention also provides a polysulfide-based flow battery, including the electrode as described above.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The non-stoichiometric nano copper sulfide catalyst of the present invention is prepared under normal temperature and pressure in liquid phase, without the need for special high-temperature and high-pressure equipment, with low production cost, and is easy to scale up for batch production, and the production cost is low.

[0025] (2) In the preparation method of the present invention, doping elements are introduced into the copper salt, and the lattice distortion is induced by the difference in doping ion radius to promote the formation of vacancies and increase the density of active sites. Through lattice modification and electronic structure regulation, the polysulfide catalytic activity and stability of the material are improved.

[0026] (3) The present invention realizes the preparation of a high-performance non-stoichiometric nano copper sulfide catalyst through a multi-parameter cooperative regulation technology. The introduction of doping elements causes lattice distortion to generate sulfur vacancies; the precise control of the sulfur / copper ion concentration (0.1 to 0.2 M) balances the reaction kinetics; the dynamic adjustment of the volume ratio (50 to 60:40 to 50) maintains the continuous excess of sulfur ions, and the slow release of the dropping rate (2 to 3 seconds / drop) inhibits the explosive nucleation, generating uniform nanoparticles. Therefore, when the prepared non-stoichiometric nano copper sulfide catalyst is used as the negative electrode of a polysulfide-based flow battery for a polysulfide-based flow battery, the polysulfide-based flow battery has a high specific capacity and energy density, excellent cycle performance, and has good commercial application prospects. Description of the Drawings

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the accompanying drawings required for the description of the embodiments or the prior art. Obviously, the accompanying drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other accompanying drawings can also be obtained based on these drawings.

[0028] Figure 1 SEM images of the nanoscale copper sulfide obtained from the reactions in Example 1, Example 2, Example 3, and Comparative Example 1 of the present invention; Figure 2 XRD patterns of the products obtained from the reactions in Example 1, Example 2, Example 3, and Comparative Example 1 of the present invention; Figure 3 Comparative cyclic voltammetry data graph of the polysulfide-based flow battery electrode prepared in Example 1 of the present invention and Comparative Example 1; Figure 4 Comparative cyclic voltammetry data graph of the polysulfide-based flow battery electrode prepared in Example 2 of the present invention and Comparative Example 1; Figure 5 Comparative cyclic voltammetry data graph of the polysulfide-based flow battery electrode prepared in Example 3 of the present invention and Comparative Example 1; Figure 6 Charge-discharge curves of the battery assembled with the polysulfide-based flow battery electrodes obtained from the reactions in Example 1, Example 2, Example 3, and Comparative Example 1 of the present invention at 50 mA / cm 2 below; Figure 7 Rate performance graph of the battery assembled with the polysulfide-based flow battery electrodes obtained from the reactions in Example 1, Example 2, Example 3, and Comparative Example 1 of the present invention; Figure 8 Long-term cycling performance graph of the battery assembled with the polysulfide-based flow battery electrodes obtained from the reactions in Example 1 and Comparative Example 1 of the present invention.

[0029] Figure 9 XRD pattern of the product obtained from the reaction in Comparative Example 2 of the present invention.

[0030] Figure 10 Long-term rate performance graph of the battery assembled with the polysulfide-based flow battery electrodes obtained from the reactions in Comparative Example 1 and Comparative Example 2 of the present invention. Detailed implementation manners

[0031] To facilitate the understanding of the present invention, the following will describe the present invention more comprehensively and meticulously in combination with the accompanying drawings of the specification and preferred embodiments. However, the protection scope of the present invention is not limited to the following specific embodiments.

[0032] Unless otherwise defined, all technical terms used hereinafter have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0033] Unless otherwise specifically stated, various raw materials, reagents, instruments, and equipment used in the present invention can be obtained through the market or prepared by existing methods.

[0034] Example 1: A method for preparing non-stoichiometric nano copper sulfide of the present invention includes the following steps: (1) Weigh 6 mmol of a sulfur ion-containing compound (Na2S·9H2O), dissolve it in 60 ml of deionized water under the condition of constant temperature magnetic stirring at 30°C, and adjust the pH to 12 using sodium hydroxide to obtain a solution denoted as solution A.

[0035] Weigh 5 mmol of copper nitrate trihydrate (Cu(NO3)3·3H2O), 0.15 mmol of silver nitrate, and 2.5 mmol of zinc nitrate, dissolve them in 50 ml of deionized water under the condition of constant temperature magnetic stirring at 30°C, and adjust the pH to 2 using dilute nitric acid to obtain a solution denoted as solution B.

[0036] (2) Transfer solution B to a separatory funnel, keep solution A under stirring at a stirring speed of 500 r / min, fix the separatory funnel above solution A for titration, maintain the titration rate at 2 s / drop, and stir at room temperature until the titration is complete to obtain a suspension C.

[0037] (3) Let the suspension C stand for 1 h, filter it three times with deionized water and ethanol respectively, collect the black precipitate, finally dry it in an oven at 80°C for 24 h, and then grind it in a mortar for 10 min to obtain a non-stoichiometric nano copper sulfide material.

[0038] The SEM image of the non-stoichiometric nano copper sulfide material prepared in this example is shown in Figure 1 , and its XRD is shown in Figure 2 , and the electrochemical performance is as shown in Figure 3 , Figures 6 - 8 shown.

[0039] Example 2: A method for preparing non-stoichiometric nano copper sulfide includes the following steps: (1) Weigh 6 mmol of a sulfur ion-containing compound (Na2S·9H2O), dissolve it in 60 ml of deionized water under the condition of constant temperature magnetic stirring at 30°C, and adjust the pH to 12 using sodium hydroxide to obtain a solution denoted as solution A.

[0040] Weigh 5 mmol of copper nitrate trihydrate (Cu(NO3)3·3H2O) and 0.05 mmol of silver nitrate, dissolve them in 50 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 2 with dilute nitric acid. The resulting solution is denoted as solution B.

[0041] (2) Then transfer solution B to a separatory funnel, keep solution A under stirring at a stirring speed of 500 r / min, fix the separatory funnel above solution A for titration, maintain the titration rate at 2 s / drop, and stir at room temperature until the titration is complete to obtain suspension C.

[0042] (3) Let suspension C stand for 1 h, filter it three times with deionized water and ethanol respectively, collect the black precipitate, finally dry it in an oven at 80 °C for 24 h, and then grind it in a mortar for 10 min to obtain non-stoichiometric copper sulfide nanomaterials.

[0043] The SEM image of the non-stoichiometric copper sulfide nanomaterials prepared in this example is shown in Figure 1 and its XRD is shown in Figure 2 and the electrochemical performance is as shown in Figure 4 、 Figure 6 、 Figure 7 .

[0044] Example 3: A preparation method of non-stoichiometric copper sulfide nanomaterials, comprising the following steps: (1) Weigh 6 mmol of a sulfur ion-containing compound (Na2S·9H2O), dissolve it in 60 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 12 with sodium hydroxide. The resulting solution is denoted as solution A.

[0045] Weigh 5 mmol of copper nitrate trihydrate (Cu(NO3)3·3H2O), 1.25 mmol of zinc nitrate and 3 mmol of iron nitrate, dissolve them in 50 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 2 with dilute nitric acid. The resulting solution is denoted as solution B.

[0046] (2) Transfer solution B to a separatory funnel, keep solution A under stirring at a stirring speed of 500 r / min, then fix the separatory funnel above solution A for titration, maintain the titration rate at 2 s / drop, and stir at room temperature until the titration is complete to obtain suspension C.

[0047] (3) Let suspension C stand for 1 h, filter it three times with deionized water and ethanol respectively, collect the black precipitate, finally dry it in an oven at 80 °C for 24 h, and then grind it in a mortar for 10 min to obtain non-stoichiometric copper sulfide nanomaterials.

[0048] The SEM image of the non-stoichiometric copper sulfide nanomaterial prepared in this example is shown in Figure 1 , and its XRD is shown in Figure 2 , and the electrochemical performance is as shown in Figure 5 , Figure 6 , Figure 7 .

[0049] Comparative Example 1: A preparation method of non-stoichiometric copper sulfide nanomaterial, comprising the following steps: (1) Weigh 6 mmol of a sulfur ion-containing compound (Na2S·9H2O), dissolve it in 60 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 12 with sodium hydroxide to obtain a solution denoted as Solution A.

[0050] Weigh 5 mmol of copper nitrate trihydrate (Cu(NO3)3·3H2O), dissolve it in 50 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 2 with dilute nitric acid to obtain a solution denoted as Solution B.

[0051] (2) Transfer Solution B to a separatory funnel, keep Solution A under stirring at a stirring speed of 500 r / min, fix the separatory funnel above Solution A for titration, maintain the titration rate at 2 s / drop, and stir at room temperature until the titration is complete to obtain a suspension C.

[0052] (3) Let the suspension C stand for 1 h, filter it three times with deionized water and ethanol respectively, collect the black precipitate, finally dry it in an oven at 80 °C for 24 h, and then grind it in a mortar for 10 min to obtain the non-stoichiometric copper sulfide nanomaterial.

[0053] The SEM image of the non-stoichiometric copper sulfide nanomaterial prepared in this comparative example is shown in Figure 1 , and its XRD is shown in Figure 2 , and the electrochemical performance is as shown in Figures 3 - 8 , Figure 10 .

[0054] Comparative Example 2: A preparation method of non-stoichiometric copper sulfide nanomaterial, comprising the following steps: (1) Weigh 6 mmol of a sulfur ion-containing compound (Na2S·9H2O), dissolve it in 60 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 12 with sodium hydroxide to obtain a solution denoted as Solution A.

[0055] Weigh 5 mmol of copper nitrate trihydrate (Cu(NO3)3·3H2O), dissolve it in 50 ml of deionized water under the condition of constant temperature magnetic stirring at 30 °C, and adjust the pH to 2 with dilute nitric acid to obtain a solution denoted as Solution B.

[0056] (2) Transfer solution B to a separatory funnel, keep solution A under stirring at a stirring speed of 500 r / min, fix the separatory funnel above solution A for titration, such that the liquid drops fall continuously, stir at room temperature until the titration is complete to obtain suspension C.

[0057] (3) Let suspension C stand for 1 h, filter it three times with deionized water and ethanol respectively, collect the black precipitate, finally dry it in a drying oven at 80 °C for 24 h, and then grind it in a mortar for 10 min to obtain the product.

[0058] The XRD of the non-stoichiometric nano copper sulfide material prepared in this comparative example is shown in Figure 9 , and the electrochemical performance is as shown in Figure 10 .

[0059] Performance Test A preparation method for the negative electrode of a polysulfide-based flow battery, comprising the following steps: S1. Respectively disperse the copper sulfide materials prepared in each example and comparative example as catalysts into a mixed solvent of ethanol and Nafion (volume ratio 80:1), and perform ultrasonic dispersion for 30 min; S2. Uniformly drop the dispersed slurry onto an untreated carbon felt electrode, and the mass content of the slurry is 3.2 mg / mL. To make the results comparable, the slurry concentrations in each case are kept consistent; S3. Transfer the untreated carbon felt electrode after the dropping in S2 to an oven and dry it at 60 °C for 12 h to obtain the electrode.

[0060] Battery Assembly: The comparison of the rate performance of the polysulfide-based flow batteries assembled with the electrodes prepared in each example and comparative example and the original carbon felt electrode is as shown in Figure 5 . The positive electrode of the battery is an untreated electrode, and the negative electrode is the electrode loaded with the catalyst; the positive electrode electrolyte is 0.3 M K3Fe(CN)6, the negative electrode electrolyte is 0.5 M Na2S2, and the supporting electrolytes for the positive and negative electrode electrolytes are both 2 M NaOH; the separator is Nafion212; the volumes of the electrolytes selected for the positive and negative electrodes are both 50 mL; the selected charge and discharge cut-off voltages are 0.6~1.4 V; the test current density range is 20~80 mA / cm 2 , the current density interval is 20 mA / cm 2 , and the final test current density is 20 mA / cm 2 , and the test sequence current density is from small to high.

[0061] Result Analysis From Figure 1 and Figure 2It can be seen that the copper sulfide synthesized by the method of the present invention is at the nanometer scale, the particle size is less than 100 nm, and there are no other miscellaneous peaks in the XRD characterization, indicating a high purity; the key characteristic peaks show a shift, indicating that silver ions have been successfully incorporated into CuS. From Figure 3 and Figure 4 and Figure 5 it can be seen that for the batteries assembled with the carbon felt loaded with copper sulfide catalyst in Examples 1, 2, and 3, compared with Comparative Example 1, the peak potential difference is reduced. For the first pair of redox peak potential differences of S4 2- / S2 2- they are 0.203 V, 0.276 V, and 0.191 V respectively, all less than 0.403 V of Comparative Example 1; while for the second pair of redox peak potential differences of S6 2- / S4 2- they are 0.165 V, 0.163 V, and 0.157 V respectively, all less than 0.281 V of Comparative Example 1. Moreover, the redox peak currents of each example have also increased significantly. For example, for the first pair of reduction peak current densities of Example 1 compared with Comparative Example 1, it increased from 0.028 A / cm 2 to 0.039 A / cm 2 , and for the second pair of reduction peak current densities, it increased from 0.019 A / cm 2 to 0.028 A / cm 2 , and the ratio of the oxidation peak current density to the reduction peak current density increased from 0.51 to 1.05, getting closer to 1. This shows that the catalyst material synthesized by the present invention improves the activity and reversibility of the electrode towards the redox of polysulfides.

[0062] From Figure 6 it can be seen that for the batteries assembled with the carbon felt loaded with the catalyst in Examples 1, 2, and 3, compared with Comparative Example 1, the overpotential during the charge-discharge process is smaller. From Figure 7 it can be seen that for the batteries assembled with the carbon felt loaded with the catalyst in Examples 1, 2, and 3, compared with Comparative Example 1, there is an improvement at each current density, and the improvement is most obvious at the current density of 80 mA / cm 2 . The energy efficiencies of each example at the current density of 80 mA / cm 2 are 70.5%, 66.7%, and 65.9% respectively, while the energy efficiency of Comparative Example 1 at the current density of 80 mA / cm 2 is only 51.5%, and the batteries of each example operate more stably. From Figure 8It can be seen that, compared with Comparative Example 1, the battery assembled with the supported catalyst carbon felt in Example 1 has greatly improved long-cycle stability. The number of stable operation cycles of the battery has increased from less than 150 cycles originally to about 700 cycles in Example 1; the capacity decay per cycle has also decreased from 0.045% in Comparative Example 1 to 0.0035% in Example 1. From Figure 9 It can be seen that if the dropping rate of Solution B into Solution A is increased, it will cause the generated product to be multiphase, and more Cu9S5 will be mixed in the obtained CuS; from Figure 10 It can be seen that the performance of the CuS mixed with Cu9S5 obtained in Comparative Example 2 is not good. Although the energy efficiency has increased from 62.9% to 71.4% at a current density of 20 mA / cm 2 compared with the original carbon felt, it is far lower than 83.3% in Comparative Example 1. Moreover, when the current density is greater than 60 mA / cm 2 the battery cannot operate.

[0063] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. And each technical feature of the above embodiments can be arbitrarily changed, combined, substituted, modified, and simplified, but should be regarded as an equivalent replacement method and should be included in the protection scope of the present invention.

Claims

1. A preparation method of non-stoichiometric nano copper sulfide, characterized in that, It includes the following steps: (1) Prepare a solution of a sulfur ion-containing compound to obtain a first precursor solution; (2) Prepare a solution of a copper salt and a salt containing a doping element to obtain a second precursor solution; (3) Drop the second precursor solution into the first precursor solution while continuously stirring the first precursor solution; (4) Filter the reactant obtained in step (3) to obtain the non-stoichiometric nano copper sulfide.

2. The preparation method according to claim 1, characterized in that, In step (1), the pH value of the first precursor solution is 11 to 13; the pH of the first precursor solution is adjusted using sodium hydroxide or potassium hydroxide solution.

3. The preparation method according to claim 1, characterized in that, In step (2), the pH value of the second precursor solution is 1.5 to 2.5; the pH of the second precursor solution is adjusted using dilute nitric acid.

4. The preparation method according to claim 1, wherein The sulfur ion-containing compound is selected from at least one of sodium sulfide, potassium sulfide, or ammonium sulfide; The copper salt is selected from at least one of copper sulfate, copper nitrate, or copper chloride; The salt containing a doping element is selected from at least one of zinc sulfate, zinc nitrate, zinc chloride, magnesium nitrate, aluminum nitrate, aluminum sulfate, aluminum chloride, iron nitrate, iron sulfate, iron chloride, manganese nitrate, manganese sulfate, or silver nitrate.

5. The preparation method according to claim 1, wherein In step (2), the molar ratio of the copper salt to the salt containing a doping element is 1:0.001 to 1:0.

8.

6. The preparation method according to claim 1, characterized in that, The concentration of the sulfur ion-containing compound in the first precursor solution is 0.1 to 0.2 M; The concentration of the copper salt in the second precursor solution is 0.1 to 0.2 M.

7. The preparation method according to claim 1, characterized in that, In step (3), the volume ratio of the first precursor solution to the second precursor solution is (50 - 60):(40 - 50); The dropping rate of the second precursor solution is 2 to 3 seconds per drop; the stirring rate is 450 to 550 r / min.

8. The preparation method according to any one of claims 1 to 7, characterized in that, In step (3), the precipitate obtained after filtration is dried and ground. Among them, the drying temperature is 50 to 80 °C, the drying time is 22 to 26 h; the grinding time is 10 to 15 min.

9. A negative electrode of a polysulfide-based flow battery, characterized in that, It includes non-stoichiometric nano copper sulfide prepared by the preparation method described in any one of claims 1 to 8.

10. A polysulfide-based flow battery, characterized in that, It includes the negative electrode described in claim 9.